Analysis of the Feasibility of the OrthoNail Hybrid Intramedullary Implant in the Human Body with Respect to Material Durability - Dominika Grygier; Piotr Kowalewski; Mariusz Opałka; Jakub J. Słowiński; Mateusz Dziubek; Dariusz Pyka (Journal of Functional Biomaterials)
This study focuses on the development and evaluation of the OrthoNail hybrid intramedullary implant for lower limb lengthening in patients requiring significant skeletal reconstruction. The implant addresses the challenges in load-bearing during rehabilitation, providing a robust solution that is capable of supporting physiological loads. Mechanical tests, including axial compression, tension, torsion, and 3,4-point bending, determined the implant’s load capacity and fatigue resistance, while finite element analysis assessed stress distributions in bone tissue and around screw holes during single-leg stance, with boundary conditions derived from Orthoload database data. The OrthoNail implant demonstrated excellent mechanical stability, sustaining torsional loads of up to 19.36 Nm at maximum elongation (80 mm) and 17.16 Nm at zero elongation. Under axial compression, it withstood forces of up to 1400 N, maintaining structural integrity. Fatigue testing revealed resilience under dynamic loading conditions for over 1,000,000 cycles at a load of 500 N, with no mechanical failure or material degradation observed. Stress concentrations near screw holes indicate areas for potential optimization. The findings indicate that the OrthoNail implant demonstrates excellent mechanical stability and is well-suited for clinical application, enabling early full weight-bearing during rehabilitation.